Physical education program in a competency-based approach in secondary school in Benin - TAOUEMA, Bienvenu; AHONNON, Adolphe; GNARIGO, A. (My University, 2023)
This historical study, but which leaves room for an intrusion of sociology, is part of the concern about the evolution of physical education and sports programs, since the adoption of the competency-based approach as a new teaching modellearning. The research question was: Has there been significant progress, in terms of pedagogical teaching programs for PE, in secondary school, that can be noted since the advent of the competency-based approach? On this subject, we have put forward ; the following research hypothesis: the Beninese secondary school is very rich in PE programs since the new reforms and the advent of the competency-based approach. And to test this hypothesis, we had the general objective of exposing the changes and progress known by the teaching of physical education in terms of study programs since the advent of the APC. And we have as specific objectives : to expose all the PE programs developed since the first program of the APC era; and analyze progress in the occurrence of programs. This qualitative study conducted in the field through documentary research and interviews resulted in a confirmation of our hypothesis. Concretely, concerning physical education and sports, the new programs of the skills-based approach began with the first form in 2005, with their application guides. And gradually from the sixth to the terminal from 2005 to 2011 each class had its program and its Guide. After observing a break in 2012, the same scenario resumed from first form in 2013, to arrive in seventh (7th) class in 2019 where this time a report was ordered in 2020 and delivered in 2021 This report was presented in 2021 at a national symposium. In the end, PE in Benin is rich in school programs for each class from the sixth to the final year, and these programs have even experienced a rapid grooming without it being known, unfortunately, for what reasons, on what bases, to correct what and to make what improvements ?
Keywords: Physical education; evolution; program; advent; competency-based approach